PENGEMBANGAN LKM KIMIA INSTRUMENTASI BERBASIS KEARIFAN LOKAL PADA PRAKTIKUM ANALISIS KUALITATIF FLAVONOID DENGAN SPEKTROFOTOMETRI UV-VISIBEL - Effendy, Mutiara; Masriani, Masriani; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine feasibility and student response to worksheet of instrumentation chemical practicum based on local wisdom. It is developed based on test results the expert (expert judgment) and field trials. This research method was the research and development (R&D) which adopt a development model Borg & Gall. Subject of this research is a chemistry student worksheet based on local wisdom that tested the students of Chemistry Education FKIP Tanjungpura University in early trials and major field trials. The results of data analisis showed that chemistry student worksheet based on local wisdom is very proper to use in learning of the content feasibility of 93,33%, presentation feasibility of 91,67%, linguistic feasibility of 93,33%, chart feasibility of 91,67%. The student response initial field trials of 86,16%, and the main field trials of 81,04%. It showed that the level of chemistry student worksheet based on local wisdom belongs to very high criteria.    Keywords: Student worksheet, Local wisdom, UV-Visible spectrophotometry